2014
DOI: 10.1002/jpln.201200581
|View full text |Cite
|
Sign up to set email alerts
|

Ligands involved in Pb immobilization and transport in lettuce, radish, tomato and Italian ryegrass

Abstract: Lead (Pb) and other heavy metals represent a great source of concern in agriculture because they may disperse from polluted sources and accumulate in crop organs. This research study was performed with three edible crops and one pasture species (lettuce: Lactuca sativa L. cv. Romana; radish: Raphanus sativus L. var. radicicola; tomato: Lycopersicon lycopersicum L. Karst.; Italian ryegrass: Lolium multiflorum Lam). It was aimed at (1) assessing how species affect Pb distribution among plant organs, (2) determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Plant roots are considered as the most vulnerable tissue, with a direct correlation with the uptake of HMs from soil solution. It was reported that radish roots and hypocotyls accumulated a large amount of Pb, especially in roots, which accounted for almost 50% of the total lead content of the plant 23 , 24 . Hence, it is of great importance to reduce the Pb content and dissect the molecular mechanism of Pb detoxification in radish.…”
Section: Introductionmentioning
confidence: 99%
“…Plant roots are considered as the most vulnerable tissue, with a direct correlation with the uptake of HMs from soil solution. It was reported that radish roots and hypocotyls accumulated a large amount of Pb, especially in roots, which accounted for almost 50% of the total lead content of the plant 23 , 24 . Hence, it is of great importance to reduce the Pb content and dissect the molecular mechanism of Pb detoxification in radish.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in callose content in response to stress generally limits primary root growth [51]. Lead transport from roots to the leaves was immobilised by the formation of Pb complexes with organic acids (carboxylic and amino acids), affecting Pb mobility in plant vessels [52]. Additionally, Pb availability in the roots is affected by the presence of other TEs.…”
Section: Accumulation and Translocation Of CD Pb And Zn In Carrotsmentioning
confidence: 99%
“…Among the published works based on measurements performed at the beamline in the last few years, we point out the investigation of Tl contamination of the drinkable water from the public distribution system of Valdicastello Carducci-Pietrasanta (northern Tuscany, Italy) [9]; the study of As contamination of floodplain soils and groundwater from shallow aquifers [10,11]; the study of Fe chemical environment in asbestos and erionite mineral fibers [12]; the investigation of selenium (Se) and lead (Pb) accumulation, distribution, and speciation in edible plants [13,14]; the Fe speciation in urban particulate matter and industrial quartz dusts [15,16]; the investigation of amorphous zinc (Zn) biomineralization ("white mud"), occurring at Naracauli stream, Sardinia [17]; the Sb speciation in brake linings, brake pad wear residues, road dust, and atmospheric particulate matter [18]; the interaction of As-rich natural pyrite with aqueous selenite [Se (IV)] [19], and As speciation in travertines [20].…”
Section: Recent Research In Environmental Sciencementioning
confidence: 99%